Coronary artery compression during intention to treat right ventricle outflow with percutaneous pulmonary valve implantation: Incidence, diagnosis, and outcome. Issue 7 (19th March 2014) - Fraisse, Alain; Assaidi, Anass; Mauri, Lucia; Malekzadeh‐Milani, Sophie; Thambo, Jean‐Benoit; Bonnet, Damien; Iserin, Laurence; Mancini, Julien; Boudjemline, Younes
<x xml:space="preserve">Abstract</x> Objectives Evaluate the incidence, diagnosis, and outcome of coronary compression (CC) during right‐ventricular outflow tract interventions. Background The incidence, risk factors, diagnosis, and outcomes of CC during percutaneous pulmonary valve implantation are poorly defined. Methods One‐hundred consecutive patients (May 2008 to January 2012) undergoing transcatheter right‐ventricular outflow tract treatment in two institutions were studied. Results CC occurred in six patients (6%) with a right ventricular outflow conduit stenosis, at a median age of 24.5 (13–49) years. It involved the left main coronary artery in four and the right coronary artery originating from the left anterior descending coronary artery in two patients. Conduit types were homograft (n = 3), bioprosthesis (n = 2), and a pericardial patch (n = 1). Median diameter was 23 (17–24) mm at surgical implantation. CC was diagnosed through a selective coronary angiogram during balloon dilation of the conduit in the first three patients and through an aortic root angiogram for the three next cases because we recognized that proximal compression could be masked during coronary artery cannulation. It was suspected on pre‐procedure imaging (magnetic resonance imaging and/or computed tomography) in three cases. Patients with abnormal coronary anatomy tend to be at increased risk of CC (P = 0.0504). One institution had a higher incidence of CC (P = 0.04). CC resolved after balloon deflation. No patient underwent conduit stenting. Four patients underwent surgical reconstruction of right ventricular outflow tract. Conclusions CC is accurately diagnosed during right‐ventricular outflow tract interventions. We recommend an aortic root angiogram during dilation with a non‐compliant balloon matching the diameter and length of the intended conduit implant. © 2014 Wiley Periodicals, Inc.